Murdered Elder Indigenous Women and Legal Outcomes - Burgess, Ann W.; Petreca, Victor; Brucato, Gary; Hoblock, Courtney; Mars, Mak; Lamade, Raina V.; Dowdell, Elizabeth B. (Journal of interpersonal violence, 2025)
This qualitative descriptive analysis examines 33 cases of missing and murdered Indigenous women aged 50 years and older. The cases encompassed single murders, multiple murders, and mass stabbing events. The study found that the offender was known and/or identified in the majority of cases, with a significant portion resulting in guilty pleas or jury convictions. However, a notable portion of cases remained unsolved or ended with the offender’s suicide. Alcohol and/or illicit substance abuse was prevalent; known substance abuse history was identified in victim and/or offender for nearly 70% of cases. Most murders occurred off tribal land and were perpetrated by men, typically younger than their victims, with some form of relationship to them. Themes for the resolved cases varied, including familial violence, sexual violence, and financial gain. The findings underscore the need for intervention strategies such as addressing substance abuse in adolescence, intervening early in relationship conflicts, training law enforcement in elder sexual homicide investigations, and providing clinical care for mental illness in cases involving family and partners. Additionally, the study highlights the necessity for a national database to track homicides involving elder Indigenous women, facilitating more effective prevention and response efforts.